1998
DOI: 10.1161/01.cir.97.10.958
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Importance of Emotional Support for Elderly Patients Hospitalized With Heart Failure

Abstract: Among elderly patients hospitalized with clinical heart failure, the absence of emotional support, measured before admission, is a strong, independent predictor of the occurrence of fatal and nonfatal cardiovascular events in the year after admission. In this cohort, the association is restricted to women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
209
4
6

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 310 publications
(227 citation statements)
references
References 28 publications
8
209
4
6
Order By: Relevance
“…99 Table 5 lists 11 studies evaluating the relationship between social factors and prognosis in patients with preexisting CAD. [113][114][115][116][117][118][119][120][121][122][123] Significant prognostic relationships are present in most of these studies, and the risk ratios are substantial. For instance, Berkman et al 119 observed a nearly 3-fold increase in subsequent cardiac events in post-MI patients reporting a low level of emotional support, and Williams et al 118 observed a similar 3-fold increase in mortality over 5 years among CAD patients who were unmarried or had no significant confidant in their life.…”
Section: Social Isolation and Lack Of Social Supportmentioning
confidence: 99%
“…99 Table 5 lists 11 studies evaluating the relationship between social factors and prognosis in patients with preexisting CAD. [113][114][115][116][117][118][119][120][121][122][123] Significant prognostic relationships are present in most of these studies, and the risk ratios are substantial. For instance, Berkman et al 119 observed a nearly 3-fold increase in subsequent cardiac events in post-MI patients reporting a low level of emotional support, and Williams et al 118 observed a similar 3-fold increase in mortality over 5 years among CAD patients who were unmarried or had no significant confidant in their life.…”
Section: Social Isolation and Lack Of Social Supportmentioning
confidence: 99%
“…Kaplan et al, 1994;Orth-Gomer, Rosengren, & Wilhelmsen, 1993;Pennix et al, 1997;Seeman et al, 1993;Vogt, Mullooly, Ernst, Pope, & Hollis, 1992). Social isolation is particularly unhealthy in patients with preexisting CHD (Angerer et al, 2000;Berkman, Leo-Summers, & Horwitz, 1992;Case, Moss, Case, McDermott, & Eberly, 1992;Gorkin et al, 1993;Horsten et al, 2000;Krumholz et al, 1998;Welin, Lappas, & Wilhelmsen, 2000;R. B. Williams et al, 1992;Woloshin et al, 1997), although different indicators of support and isolation sometimes produce inconsistent effects (Irvine et al, 1999).…”
Section: Social Isolation and Conflictmentioning
confidence: 99%
“…Although the direction of causation underlying this correlation remains somewhat controversial, it seems quite likely that health is an important determinant of subjective well-being. In turn, a large and growing literature suggests that physical health itself is strongly conditioned by social factors, so it is plausible to conjecture that health constitutes one pathway through which social factors influence subjective well-being (Berkman & Glass 2000;House et al 1982;Reed et al 1983;Schoenbach et al 1986;Seeman et al 1993;Sugisawa et al 1994;Farmer & Stucky-Ropp 1996;Kessler & Essex 1997;Roberts et al 1997;Krumholz et al 1998;Kawachi & Berkman 2000;Kawachi & Kennedy 1997;Ryff & Singer 2003). Although not exploring directly the putative impact of health on subjective well-being, our analysis here does include self-reports on physical health, as a way of estimating the possible indirect effects of social factors on subjective well-being.…”
Section: Introductionmentioning
confidence: 99%